PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN PENDEKATAN COOPERATIVE LEARNING TIPE NUMBERED-HEAD-TOGETHER (NHT) - Diani, Sutris (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The research is research do it in the class is background by social lesson still sentral to teacher so that student a little active. This research uses kualitatif and kuantitatif approach. Process learning are draf, execute, control and reflection. The result to shows that appying approximation cooperative learning tipe NHT can to increase result the student learning in social lesson. Marking from learning lesson in the first cycle is 83,5%. The second cycle increases become 97%. The result abservation of teacher activity in the firs cycle is 91,5% and increase become 98% in the second cycle. The level of complete in the result study in the first cycle is 83% and increases become 95% in the second cycle. Complete level to result student in learning increase from average in first cycle is 73,46 became 83,84 in second cycle.   Kata kunci: Hasil Belajar, Pembelajaran IPS, Pendekatan Cooperative  Learning tipe Numbered-Head-Together (NHT)